A Systems Thinking Approach to Inform Coherent Policy Action for NCD Prevention; Comment on "How Neoliberalism Is Shaping the Supply of Unhealthy Commodities and What This Means for NCD Prevention" - Penelope Milsom; Richard Smith; Helen Walls (Kerman University of Medical Sciences, 2020)
Lencucha and Thow tackle the enormous public health challenge of developing non-communicable disease (NCD) policy coherence within a world structured and ruled by neoliberalism. Their work compliments scholarship on other causal mechanisms, including the commercial determinants of health, that have contributed to creating the risk commodity environment and barriers to NCD prevention policy coherence. However, there remain significant gaps in the understanding of how these causal mechanisms interact within a whole system. As such, public health researchers' suggestions for how to effectively prevent NCDs through addressing the risk commodity environment tend to remain fragmented, incomplete and piecemeal. We suggest this is, in part, because conventional policy analysis methods tend to be reductionist, considering causal mechanisms in relative isolation and conceptualizing them as linear chains of cause and effect. This commentary discusses how a systems thinking approach offers methods that could help with better understanding the risk commodity environment problem, identifying a more comprehensive set of effective solutions across sectors and its utility more broadly for gaining insight into how to ensure recommended solutions are translated into policy, including though transformation at the paradigmatic level.